Early and late complications after gastric bypass: A literature review - Nevmerzhytskyi, V. O. (General Surgery, 2021)
Over the last few decades, excess weight and obesity have become a considerable health problem that has a lasting impact on communities worldwide. According to the WHO, about 1.9 billion people over the age of 18 are overweight [32]. Obesity accounted for about 4.7 million premature deaths in 2017. Globally, obesity was associated with an increase in mortality rate from 4.5 % in 1990 to 8 % in 2017 [32]. Bariatric surgery is currently recognized as the most effective treatment option for morbid obesity. Over the past 10 years, gastric bypass surgery has proved more effective than any other surgical methods due to its optimal metabolic effects. The aim of the review is to carry out an analysis of literature data in order to identify main complications after gastric bypass in patients with obesity. The complication rate after bariatric surgery decreased from 10.5 % in 1993 to 7.6 % in 2006 [3]. The mortality rate after bariatric surgery was 0.08 % within 30 days after surgery and 0.31 % after 30 days [13]. According to the BOLD study (2010), for 57,918 bariatric operations, the complication rate was 6,240 (10.77 %) and the mortality rate was 78 (0.135 %), within 30 days after surgery — 0.089 %, within 90 days after surgery — 0.112 %. Roux‑en‑Y Gastric Bypass (RYGB) was carried out in 30,864 cases, and 4,588 (14.87 %) patients developed postoperative complications. Early complications include anastomotic leaks (0 — 5,6 % for laparoscopic approach and 1,6 — 2,6 % — for laparotomy), small bowel obstruction caused by a blood clot (0 — 0,5 %), bleeding from the sutures (1,5 %), and thromboembolic complications (0,2 — 5 %). Late complications include stenosis of the gastrointestinal tract (3 — 27 %), marginal ulceration (MU) — 0,6 — 16 %, an incarcerated Petersen’s space hernia — 2,51 %, perforation of the stomach and small intestine (1 — 2 %), gastrogastric fistula formation — 1,5 — 6,0 %, weight regain (to 17,1 %). Increasing global demand for bariatric surgery as the best option for the management of excess weight and obesity necessitates more detailed investigation of possible complications it may induce. Therefore, further research is required to develop and study new effective methods for prevention and treatment of complications after surgical treatment of patients with morbid obesity.